Expressway 5G-V2X:technology,solution and application - Dongsheng WU; Chuanqi WANG; Wei JIN; Fengna LI (Dianxin kexue)
5G-V2X is widely used in the fields of automatic driving,intelligent transportation and smart city.Expressway is one of the typical traffic scenes.The technology,solution and application of 5G-V2X in the expressway scene was explored.Through the construction of “perception,communication and computing” three technical capabilities,the scheme of expressway 5G-V2X was proposed.At last,the typical applications such as the application of expressway logistics and the application of expressway congestion control were introduced.